2020
DOI: 10.1016/j.cmi.2020.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of viral quasispecies during SARS-CoV-2 infection

Abstract: Objectives Studies are needed to better understand the genomic evolution of the recently emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to describe genomic diversity of SARS-CoV-2 by next-generation sequencing (NGS) in a patient with longitudinal follow-up for SARS-CoV-2 infection. Methods Sequential samples collected between January 29th and February 4th, 2020, from a patient infected by SARS-CoV-2 were used to perform amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 16 publications
10
106
0
4
Order By: Relevance
“…Yet, no significant nucleotide differences (signature) were detected between URT and LRT variants in the S glycoprotein. Similar results have been reported with characterization of quasispecies differences between anatomical sites (URT vs. LRT), but also from one day to the next with sequential samples from a single patient, suggesting a complex dynamic distribution of variants ( 76 ). It has been recently reported that SARS-CoV-2 can be detected in multiple organs including pharynx, liver, pancreas, kidneys, heart and brain ( 77 , 78 ).…”
Section: Tissue-specific Patterns Of Sars-cov-2 Variantssupporting
confidence: 86%
“…Yet, no significant nucleotide differences (signature) were detected between URT and LRT variants in the S glycoprotein. Similar results have been reported with characterization of quasispecies differences between anatomical sites (URT vs. LRT), but also from one day to the next with sequential samples from a single patient, suggesting a complex dynamic distribution of variants ( 76 ). It has been recently reported that SARS-CoV-2 can be detected in multiple organs including pharynx, liver, pancreas, kidneys, heart and brain ( 77 , 78 ).…”
Section: Tissue-specific Patterns Of Sars-cov-2 Variantssupporting
confidence: 86%
“…For each patient, the patterns of variants in URT and LRT were profoundly different, indicating compartmentalized virus replication, as previously described [12]. However, no clear variant signature for each respiratory compartment was observed, and no significant difference of LRT and URT nucleotide diversity was observed.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, structural variations of SARS-CoV-2 often lead to alternative sgRNA transcripts and significant alterations in their translation products. These variants potentially exist as quasispecies to facilitate evolutionary selection and host adaptation as observed in other RNA viral species [34][35][36][37] .…”
Section: Full-length Iso-seq Analysis Revealed Extensive Structural Vmentioning
confidence: 99%